Detection of Landfill Odour using Quartz Crystal Microbalance (QCM) - Saiful Azhar, Saad; Mohd Noor, Ahmad; Suhardy, Daud; Farizul Hafiz, Kasim; Mohd Nazry, Salleh (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my